Duration of the depressive episode is correlated with ganglion cell inner plexifrom layer and nasal retinal fiber layer thicknesses: Optical coherence tomography findings in major depression. (30th May 2016) - Yıldız, Mesut; Alim, Sait; Batmaz, Sedat; Demir, Selim; Songur, Emrah; Ortak, Hüseyin; Demirci, Kadir
Abstract: Optical coherence tomography (OCT) is a relatively new, noninvasive imaging technique that has been used increasingly to diagnose and manage a variety of retinal diseases. Since the axons in retinal nerve fiber layer (RNFL) are nonmyelinated within the retina, OCT has been used in various neurodegenerative diseases to visualize the process of neurodegeneration. Decreases in RNFL and ganglion cell inner plexiform layer (GCIPL) thicknesses were observed in patients with schizophrenia. To date, there is no clinical research investigating OCT parameters in patients with MD. We compared the RNFL thickness, GCIPL thickness in 58 MD patients and 57 healthy controls, and investigated their correlation with clinical variables of depression. Depressed patients were not different from the healthy controls with regard to OCT parameters. GCIPL and nasal RNFL were correlated with the duration of the latest depressive episode. Some measures of OCT were negatively associated with clinical variables like a family history of psychiatric diagnosis and the duration of the latest episode. Larger studies including depressed patients of different severity, including structured interviews and controlling for the effect of antidepressant treatment will provide better results. Highlights: OCT has been used in various neurodegenerative diseases to visualize the process of neurodegeneration. We assessed 58 patients with major depression and 57 healthy controls in terms of optical coherence tomography. Depressed patients were not diferent from the healthy controls with regard to OCT parameters. Ganglion cell-inner plexiform layer and nasal retinal fiber layer were correlated with the duration of the latest depressive episode.